Policy strategy in making Situbondo regency as a cassava entrepreneur city using the work breakdown structure method - Moh. Rasidi; Ramli, Ramli; Yona Wahyu Lolita; Muhammad Alif Subhan Akbar; Sigid Budianto Said (Institute of Computer Science (IOCS), 2025)
Agricultural land in Situbondo Regency is dominated by sub-optimal land with a total area of ​​21,963 ha (70% of the agricultural land area in Situbondo Regency). One alternative commodity that can be developed to optimize the function of sub-optimal is cassava. However, cassava development faces potential and opportunities, challenges and obstacles, so to making Situbondo Regency as a Cassava Entrepreneur City, an appropriate and comprehensive policy strategy is needed from the Situbondo Regency government. The purpose of this study is to formulate a Policy Strategy in Making Situbondo Regency as a Cassava Entrepreneur City, and to find out the business model for cassava development in Situbondo Regency. The method used in formulating the strategy is the Work Breakdown Structure Method. Research results show that The strategy to make Situbondo Regency a cassava entrepreneur city is Providing quality and competitive cassava in a sustainable manner, Development of an intermediate industry using Situbondo specific cassava raw materials and/or other products, and Development of a high value added industry based on cassava and its intermediate products. The business model that is suitable for developing cassava in Situbondo Regency is one that uses the principle of zero waste process, as an integrated business model.